GAYA HIDUP KONSUMSI FASHION MAHASISWA UNIVERSITAS SRIWIJAYA ASAL KABUPATEN MUARA ENIM - Vhonita, Ussy; Purnama, Dadang Hikmah (Jurnal Empirika, 2023)
This research examines the "Fashion Consumption Lifestyle of Sriwijaya University Students from Muara Enim Regency". In this modern era, fashion is no longer done to fulfil primary needs but only to gain popularity among society or higher social status, including late teens, namely Sriwijaya University students from Muara Enim Regency. They constantly update their fashion by using trendy fashion. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participant observation and documentation. This research uses Bourdieu's practice theory. The results of the study show that students at Sriwijaya University, Palembang campus, who come from Muara Enim Regency, are part of the fashion consumption lifestyle, who always consume fashion that is currently trending from local brands and well-known brands (branded) while always looking neat, fashionable and fashionable. They want to show their existence in society and to gain recognition within their circle of friends, especially within the Sriwijaya University Palembang Campus.